Islamic Insurance (Takāful): A Review Of Recent Riset and Future Directions - Ditama, Rezki Agrisa; Fauzi, Muhammad; Muid, Abdul; Mahdi, Al- (Universitas Pendidikan Indonesia, 2024)
Purpose – This riset aims to review of recent riset on Takāful and highlight future riset directions..Methodology - This riset is descriptive qualitative, with the method used is a literature review. Riset data was collected or searched through the Emerald data base for the last 24 months (January 2022 – December 2023) by entering the keyword title in the search column